2005
DOI: 10.1104/pp.104.054270
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Mediated Control of the Basic Helix-Loop-Helix Protein FER, a Regulator of Iron Uptake in Tomato

Abstract: Root iron mobilization genes are induced by iron deficiency downstream of an unknown signaling mechanism. The FER gene, encoding a basic helix-loop-helix domain protein and putative transcription factor, is required for induction of iron mobilization genes in roots of tomato (Lycopersicon esculentum). To study upstream regulatory events of FER action, we examined the control of FER gene and FER protein expression in response to iron nutritional status. We analyzed expression of the FER gene and FER protein in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 31 publications
5
70
0
Order By: Relevance
“…In higher plants, a number of transcription factors have been identified as components of the iron signaling response, including FIT1/FER, PYE, bHLH115, and ILR3 (Ling et al, 2002;Colangelo and Guerinot, 2004;Brumbarova and Bauer, 2005;Bauer et al, 2007;Dinneny et al, 2008;Jeong and Guerinot, 2009;Long et al, 2010). In addition, there is a posttranslational component involving an E3 ubiquitin ligase BTS (Long et al, 2010).…”
Section: Regulation Of Iron Homeostasismentioning
confidence: 99%
“…In higher plants, a number of transcription factors have been identified as components of the iron signaling response, including FIT1/FER, PYE, bHLH115, and ILR3 (Ling et al, 2002;Colangelo and Guerinot, 2004;Brumbarova and Bauer, 2005;Bauer et al, 2007;Dinneny et al, 2008;Jeong and Guerinot, 2009;Long et al, 2010). In addition, there is a posttranslational component involving an E3 ubiquitin ligase BTS (Long et al, 2010).…”
Section: Regulation Of Iron Homeostasismentioning
confidence: 99%
“…The Arabidopsis FRU protein (also named FIT1), a homolog of the tomato FER protein, is necessary for the activation of the ferric reductase AtFRO2 [7,18], the H + -ATPase AtAHA7 [7] and the iron transporter AtIRT1 [18] gene expression, although in the regulation of the iron transporter there is discrepancy between the results of Colangelo and Guerinot [7] and those of Jakoby et al [18]. LeFER and AtFRU expression is induced in roots in response to Fe deficiency [1,5,7,18]. Very recently, Lucena et al [23] have shown that ethylene could regulate FRO and IRT gene expression by affecting the FER (or FERlike) gene activity.…”
Section: Introductionmentioning
confidence: 51%
“…The ferric chelate reductase LeFRO1 and the metal transporter LeIRT1 and LeNRAMP1 are proposed as main func- in tomato [33] and AtbHLH29 in Arabidopsis [24,25] has already been observed. In Addition to AtbHLH29 and FER, the posttranscriptional regulation of the ferric-chelate reductase AtFRO2 and the Fe(II)-transporter AtIRT1 was also reported [14,34].…”
Section: Expression Profiles Of Atbhlh29 and The Corresponding Genes mentioning
confidence: 99%